Amyotrophic Lateral Sclerosis and Excitotoxicity: From Pathological Mechanism to Therapeutic Target - Bogaert, E.; d'Ydewalle, C.; Van Den Bosch, L. (CNS & Neurological Disorders - Drug Targets, 2010)
Glutamate-induced excitotoxicity is responsible for neuronal death in acute neurological conditions as well as in chronic neurodegeneration. In this review, we give an overview of the contribution of excitotoxicity in the pathogenesis of amyotrophic lateral sclerosis (ALS). The selective motor neuron death that is the hallmark of this neurodegenerative disease seems to be related to a number of intrinsic characteristics of these neurons. Most of these characteristics relate to calcium entry and calcium handling in the motor neurons as intracellular free calcium concentrations increase quickly due to a high glutamate-induced calcium influx in combination with a low calcium-buffering capacity. The high calcium influx is because of the presence of GluR2 lacking, calcium-permeable AMPA receptors while a low expression of calcium-binding proteins explains the low calcium-buffering capacity. In the absence of these proteins, mitochondria play an important role to remove calcium from the cytoplasm. While all of these characteristics make at least a subpopulation of motor neurons intrinsically very prone to AMPA receptor mediated excitotoxicity, this vulnerability is further increased by the disease process. Mutated genes as well as unknown factors do not only influence the intrinsic characteristics of the motor neurons, but also the properties of the surrounding astrocytes. In conclusion, excitotoxicity remains an intriguing pathological pathway that could not only explain the selectivity of the motor neuron death but also the role of surrounding non-neuronal cells in ALS. In addition, excitotoxicity is also an interesting drug-able target as indicated by the only FDA-approved drug, riluzole, as well as by a number of ongoing clinical trials.
Keywords: AMPA receptors